2018
DOI: 10.1002/mc.22872
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of euchromatin histone‐lysine N‐methyltransferase 2 sensitizes breast cancer cells to tumor necrosis factor‐related apoptosis‐inducing ligand through reactive oxygen species‐mediated activating transcription factor 4‐C/EBP homologous protein‐death receptor 5 pathway activation

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been characterized as an anti-cancer therapeutic agent with prominent cancer cell selectivity over normal cells. However, breast cancer cells are generally resistant to TRAIL, thus limiting its therapeutic potential. In this study, we found that BIX-01294, a selective inhibitor of euchromatin histone methyltransferase 2/G9a, is a strong TRAIL sensitizer in breast cancer cells. The combination of BIX-01294 and TRAIL decreased cell viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…KMT2D is associated with low proliferation rates and sensitivity of pancreatic cancer cells to the antimetabolite 5-fluorouracil (5-FU)[15,47]. However, little is known regarding the relationship between histone methyltransferases and the ER stress pathway[48-51]. We also analyzed the expression levels of the PERK/eIF2a/ATF4/ CHOP signaling pathway mediators in ATF4 knockdown cells following L48H37 treatment, and found that the proteins upstream of ATF4 were unaltered, whereas those downstream were significantly decreased (Figure 3E-F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KMT2D is associated with low proliferation rates and sensitivity of pancreatic cancer cells to the antimetabolite 5-fluorouracil (5-FU)[15,47]. However, little is known regarding the relationship between histone methyltransferases and the ER stress pathway[48-51]. We also analyzed the expression levels of the PERK/eIF2a/ATF4/ CHOP signaling pathway mediators in ATF4 knockdown cells following L48H37 treatment, and found that the proteins upstream of ATF4 were unaltered, whereas those downstream were significantly decreased (Figure 3E-F).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed a link between histone methyltransferase and ER stress. The euchromatin histone-lysine N-methyltransferase 2 (EZH2) inhibitor sensitizes breast cancer cells to TRAIL by upregulating ATF4/CHOP-dependent DR5 expression in a ROS-dependent manner[51]. EZH2 inhibitors also reverse the high levels of histone 3 lysine 27 trimethylation on the IRE1 promoter, which restores IRE1 expression and impairs tumor growth[63].…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind that immunotherapy has dramatically changed the treatment paradigm of melanoma, it is interesting to note that another study demonstrated that SAHA by inducing DR5 expression on the cell surface and downregulating c-IAP-2 and Bcl-xL is able to sensitize resistant melanoma cells to human cytotoxic T-lymphocytes (CTL) [201,202]. Coordinating the up-regulation of death receptors and downregulation of cFLIP and Bcl-2 family members by HDACi (Figure 11a) has also been described to a variable extent in leukemia ([66,118,120,121,203,204], breast carcinoma [199,205], lung carcinoma [119,178,199], glioblastoma [197,206], neuroblastoma [168,207], hepatocellular carcinoma [208,209], or bladder carcinoma [119,210,211]. Regardless of the molecular mechanism, HDACi are often able to restore TRAIL-induced apoptosis in resistant cancer cells [95,125,135,137,178,185,197,200,201,202,206,207,212,213,214,215,216,217,218,219].…”
Section: Epigenetic Regulation Of Trail Proapoptotic Signalingmentioning
confidence: 99%
“…DeNicola et al (31) integrated metabolite tracing with gene expression analysis revealing that NF-E2-related factor 2 positively regulated the expression levels of PHGDH, PSAT1 and SHMT2 in SSP by targeting ATF4, which controlled the metabolic flux of glycolysis to serine, thereby supporting the production of GSH and nucleotides . Epigenetic modifiers also regulate the expression of key enzymes in the SSP (44)(45)(46). Histone H3 lysine 9 (H3K9) methyltransferase G9A is required for the transcriptional activation of key enzymes in the SSP during an active state, marked by H3K9 monomethylation, which is dependent on ATF4 (47).…”
Section: Association Of the Ssp With Cancer Cell Proliferation And Rementioning
confidence: 99%